Pilotage services in Turkey; key issues and ideal pilotage. Issue 2 (4th May 2017) - Uğurlu, Özkan; Kaptan, Mehmet; Kum, Serdar; Yildiz, Serdar
ABSTRACT: Previous studies have identified fundamental problems of pilotage organisations: pressure on commerce, improper working conditions, increasing traffic volume, and vessel size. Questioning the needs of pilots, the most important actors in pilotage services, is a key issue to ensure the safety of navigation in restricted waterways. This study, which conducts questionnaires and interviews with 71 pilots, reveals the structure of pilotage organisations and the profiles of pilots in Turkey. The survey examines pilot training infrastructure, professional experience, working conditions, tug services, pilot boats, accommodation facilities, and opportunities from operational, economic, and environmental constraints. The results indicate positive and negative aspects of existing pilotage organisations in Turkey in order to develop an ideal organisational model for pilotage in Turkey.